Progress of structural and electronic properties of diamond: a mini review. Issue 1 (2nd January 2021) - Yang, Hongchao; Ma, Yandong; Dai, Ying
Abstract: Diamond is of great importance for scientific and practical applications. It is the hardest natural material and holds potential applications in mechanics, electronics and photonics. Over the past few decades, great efforts have been paid for exploring its nature both experimentally and theoretically. Most of the recent studies on diamond are focused on their geometry stability and structural properties, while the research on electronic properties is relatively limited. Here, the recent research advances on diamond from a theoretical perspective are presented. In this mini review, we emphasize the recent breakthroughs related to the geometric and electronic properties of diamond, as well as the promising strategies for tuning their electronic properties, such as doping and constructing heterostructure. We then discuss its potential applications in electronic and optoelectronic devices. Finally, the challenges and opportunities in this field are also provided.